2010
DOI: 10.1103/physrevstper.6.010104
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns, correlates, and reduction of homework copying

Abstract: Submissions to an online homework tutor were analyzed to determine whether they were copied. The fraction of copied submissions increased rapidly over the semester, as each weekly deadline approached and for problems later in each assignment. The majority of students, who copied less than 10% of their problems, worked steadily over the three days prior to the deadline, whereas repetitive copiers (those who copied >30% of their submitted problems) exerted little effort early. Importantly, copying homework probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 8 publications
4
88
0
1
Order By: Relevance
“…These results are intuitive and hardly surprising. However, it is rather surprising and even disheartening to discover that dishonest students are comfortable with the fact that cheating hurts them (Palazzo et al, 2010). In their study, students were shown a graph at the beginning of the term clearly demonstrating a decline in performance with increased cheating behaviour, but no decline in the prevalence of cheating in the course was observed when compared with previous sessions of the course.…”
Section: Entitlement and Apathymentioning
confidence: 94%
See 4 more Smart Citations
“…These results are intuitive and hardly surprising. However, it is rather surprising and even disheartening to discover that dishonest students are comfortable with the fact that cheating hurts them (Palazzo et al, 2010). In their study, students were shown a graph at the beginning of the term clearly demonstrating a decline in performance with increased cheating behaviour, but no decline in the prevalence of cheating in the course was observed when compared with previous sessions of the course.…”
Section: Entitlement and Apathymentioning
confidence: 94%
“…Some students will elect to cheat even in classes where all students begin the course with roughly equivalent skill sets (Palazzo, Lee, Warnakulasooriya, & Pritchard, 2010). This leads to poorer learning amongst the cheaters, and subsequently higher rates of attrition.…”
Section: Foundational Knowledgementioning
confidence: 99%
See 3 more Smart Citations